Longitudinal Changes in the Macronutrient Contents of Breast Milk in the Mothers with Preterm Delivery - Farid Aleali; minoo fallahi; Mohammad Kazemian; Seyyed Hossein Fakhraee; Abolfazl Afjeh (Mashhad University of Medical Sciences, 2018)
Background: Contents of breast milk may change during the first weeks after childbirth, especially in preterm deliveries. The present study aimed to determine the macronutrient contents of breast milk in the mothers with preterm delivery. Methods: This prospective-descriptive study was conducted in Mahdieh Hospital in Tehran, Iran in 2015. Participants included the mothers with preterm delivery, whose infants had a gestational age of